a) ( x - 35 _ - 120 = 0
x - 35 = 120
x = 120 + 35
x = 155
b) 124 + ( 118 - x ) = 217
118 - x = 217 - 124
118 - x = 93
x = 118 - 93
x = 25
c) 156 - ( x + 61 ) = 82
x + 61 = 156 - 82
x + 61 = 74
x = 74 - 61
x = 13
a, x - 35 = 120
x = 120 + 35
x = 155
b, 124 + ( 118 - x ) = 217
118 - x = 217 - 124
118 - x = 93
x = 118 - 93
x = 25
c, 156 - ( x + 61 ) = 82
x + 61 = 156 - 82
x + 61 = 74
x = 74 - 61
x = 13
\(\left(x-35\right)-120=0\)
\(x-35=120\)
\(x=120+35\)
\(x=155\)
\(124+\left(118-x\right)=217\)
\(118-x=217-124\)
\(118-x=93\)
\(x=118-93\)
\(x=25\)
\(156-\left(x+61\right)=82\)
\(x+61=156-82\)
\(x+61=74\)
\(x=74-61\)
\(x=13\)
\(\left(x-35\right)-120=0\)
\(x-35=120\)
\(x=120+35=155\)